A Few MeV Laser-Plasma Accelerated Proton Beam in Air Collimated Using Compact Permanent Quadrupole Magnets - Fernando Brandi; Luca Labate; Daniele Palla; Sanjeev Kumar; Lorenzo Fulgentini; Petra Koester; Federica Baffigi; Massimo Chiari; Daniele Panetta; Leonida Antonio Gizzi (Applied Sciences, 2021)
Proton laser-plasma-based acceleration has nowadays achieved a substantial maturity allowing to seek for possible practical applications, as for example Particle Induced X-ray Emission with few MeV protons. Here we report about the design, implementation, and characterization of a few MeV laser-plasma-accelerated proton beamline in air using a compact and cost-effective beam transport line based on permanent quadrupole magnets. The magnetic beamline coupled with a laser-plasma source based on a 14-TW laser results in a well-collimated proton beam of about 10 mm in diameter propagating in air over a few cm distance.